Limited Liability Companies For Dummies, 3rd Edition - Reuting, Jennifer (--For dummies., 2019)
Become a savvy entrepreneur with your own LLC Limited Liability Companies For Dummies, 3rd Edition offers a clear, concise guide that explains the pros and cons of LLCs, and shares insider tips on everything from choosing your members and your company name to creating and filing your Articles of Organization and managing day-to-day operations. You'll find the most current, real-world advice on customizing an LLC for your specific business needs, creating a great operating agreement, keeping accurate records, and new information on federal regulations and fees that are applicable to LLCs, as well as a link to online tools, forms, and documents Most of the previous drawbacks to forming an LLC have all but disappeared with the IRS having loosened restrictions and individual states following suit. Because LLCs are now more flexible, they remain an attractive option for those launching a new business or reorganizing an existing business. This book shows how to form and tap into the power of an LLC: Keep up on the latest information on federal taxes, regulations, and fees Discover the advances in technology, including online tools that streamline the processes Get up-to-the minute documents and forms on new filing requirements Learn how to set-up a real estate LLC or an LLC among family members This hands-on guide addresses everything you need to know about LLCs, and will help you organize, launch, and run your business as a limited liability company just like the experts do! Limited Liability Companies For Dummies, 3rd Edition (9781119602187) was previously published as Limited Liability Companies For Dummies, 3rd Edition (9781118852989). While this version features a new Dummies cover and design, the content is the same as the prior release and should not be considered a new or updated product.